IMAGE OF TECHNICAL EDUCATION AND VOCATIONAL TRAINING FROM THE PERSPECTIVE OF PARENTS AND TEACHERS - Alavi, Khadijah; Md. Sail, Rahim; Awang, Abd Hair (Journal of Technical Education and Training, 2013)
The main purpose of this study is to understand the perception of the image and pride of working in the technical and vocational fields from the perspective of parents and teachers in secondary schools. This study was conducted in two zones, namely North (Kedah) and central zone (Selangor). Two schools were chosen from each zone, one from the city (Kajang) and the other one from rural (Dengkil), which are sufficient to obtain the views of parents and teachers. Purposive sampling was selected for the focus group discussions in schools with the participation of PTA members, i.e., parents, teachers, career counselors teachers. The results showed that there were two main themes, namely, positive and negative image of technical education and vocational training among parents and teachers. However, the negative image remained resilient among parents and teachers, especially in deciding on career paths in technical and vocational fields. The researcher also identified several new issues, for example, wastage of manpower in the country, among them due to the weak prerequisite set in selecting students in technical and vocational education system; Students who do not meet the Malay Language (Bahasa Melayu) prerequisite are unable to continue studying skills at higher certificate level. Students of Islamic studies and Arabic Language, students with academic excellence and girls who are interested in technical education and vocational training should be considered as a highly skilled workforce in the future. Some implications of this study were presented as suggestion in formulating policies to improve the image of technical education and vocational training.